Peran Guru Penggerak terhadap Pembentukan Sikap Spiritualitas Berbasis Nasionalisme Peserta Didik di Sekolah Menengah Pertama - Muhammad, Giantomi; Elmuna, Labib; Suhardini, Asep Dudi (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2024)
The driving teacher is the latest breakthrough from the Ministry of Education and Culture which functions as a motivator and school inspiration for students and fellow teachers. Its existence has a big influence and implications for school culture full of educational values. Global challenges are dimming existing norms, thereby weakening spiritual attitudes which give rise to various kinds of degradation, including tests for the nation's nationalist soul. A driving teacher is a figure who minimizes this and brings about change by forming a spiritual attitude based on nationalism. This research uses a qualitative approach with a case study method, with data collection techniques of observation, interviews, and documentation. The results obtained are that driving teachers are part of forming a spiritual attitude based on nationalism by playing a role in carrying out habituation, acculturation, and empowerment in a consistent and directed manner.